PENGATURAN PEMBAGIAN HARTA WARISAN TERHADAP OBJEK WARIS YANG BELUM DIBAGI MENURUT HUKUM ADAT - Mochamad Icksan (HUKMY : Jurnal Hukum, 2022)
Often look and there was news lest you go astray that is not fair so that one the heirs use criminal actions by inheritance according to desire , or division of and problems associated with the estate of inheritance which ended with a legal assistance for example through court institutions , all this aimed to achieve justice , and agreement in sharing and completing administrative another problem that deals with what they have left behind .The writing of this journal against the backdrop of the disputes between members of the family the payment inheritance , one in which there was a treasure that heir of their parents has not yet been divided heirs but is controlled by one of heirs .The purpose of writing this journal that is, to know how the division of object inheritance that has not yet been divided .Research methods that were used in writing this journal is the method juridical normative with research an approach to a problem that is used the legislation.